Halotolerance of Phytoplankton and Invasion Success of Nostocalean Cyanobacteria Under Freshwater Salinization - Izabelė Šuikaitė; Gabrielė Šiurkutė; Robert Ptacnik; Judita Koreivienė (Microorganisms, 2025)
Disturbed ecosystems are particularly susceptible to biological invasions. Increasing freshwater salinization, caused by anthropogenic factors, can alter the phytoplankton community and favour newly arrived halotolerant species. This study investigates the halotolerance of four Nostocalean cyanobacterial species—the native to Europe, Aphanizomenon gracile, and alien Chrysosporum bergii, Cuspidothrix issatschenkoi, and Sphaerospermopsis aphanizomenoides—using monoculture experiments under varying NaCl concentrations. Additionally, we performed two microcosm experiments to explore shifts in biodiversity in freshwater phytoplankton communities sourced from artificial reservoirs and assess their susceptibility to cyanobacterial invasion under salinity stress. Results showed that all Nostocalean cyanobacteria were halotolerant under mild salinities (up to 1 g/L NaCl), with Chrysosporum bergii and Sphaerospermopsis aphanizomenoides demonstrating the most salt tolerance. In the microcosm experiment, changes in community composition were driven by the halotolerance of dominant groups. Water body 1, dominated by Bacillariophytina, reduced its biomass of phytoplankton at high salinity (5 g/L NaCl), while water body 2, dominated by Chlorophytina, remained stable regardless of disturbance. Both cyanobacteria successfully invaded both halotolerant and halosensitive communities, increasing their dominance as salinity rose. Our findings suggest that anthropogenic stressors such as freshwater salinization can alter the phytoplankton community and increase a competitive advantage to certain taxa, including widespread alien cyanobacteria, potentially promoting invasions and bloom formation.